Стратегия формирования инклюзивной среды в современном вузе - Петряков, Петр Анатольевич (International Dialogues on Education Journal, 2017)
The article reveals the essence of the inclusion strategy as one of the priority strategies of organizational development of the modern university, ensuring the formation of an inclusive educational environment. The aim of this strategy is the creation of the equal opportunities university, where all students receive a qualitative higher education. Describes in detail the set of organizational, managerial and educational measures aimed at effective diversity management of the university.